2007
DOI: 10.1002/ajim.20492
|View full text |Cite
|
Sign up to set email alerts
|

Job stress and other working conditions: Relationships with smoking behaviors in a representative sample of working Australians

Abstract: These results suggest that job stress is related to smoking status at the population level, with different patterns in men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
2
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 39 publications
3
61
2
5
Order By: Relevance
“…A exclusão social também está presente nas formas de trabalho precárias, pois situações ou percepções de instabilidade, ausência de perspectiva no trabalho, longas jornadas ou jornadas muito restritas de trabalho, podem levar a insatisfações, favorecendo a adoção de comportamentos que reduzem momentaneamente as tensões, como o tabagismo e o álcool, entre outros. Condições psicossociais adversas no ambiente de trabalho foram positivamente relacionadas ao tabagismo em estudos já realizados 40,41 .…”
Section: Discussionunclassified
“…A exclusão social também está presente nas formas de trabalho precárias, pois situações ou percepções de instabilidade, ausência de perspectiva no trabalho, longas jornadas ou jornadas muito restritas de trabalho, podem levar a insatisfações, favorecendo a adoção de comportamentos que reduzem momentaneamente as tensões, como o tabagismo e o álcool, entre outros. Condições psicossociais adversas no ambiente de trabalho foram positivamente relacionadas ao tabagismo em estudos já realizados 40,41 .…”
Section: Discussionunclassified
“…All of these studies were based on between-person analysis. The three studies (Steptoe et al, 1998;Shields, 1999;Radi et al, 2007) which found a relationship between working time and smoking appeared as outliers, with the preponderance of evidence suggesting that long working hours did not cause increased propensities to smoke.…”
Section: Comparisons With Previous Studiesmentioning
confidence: 99%
“…This study identified a u-shaped relationship between smoking intensity and overtime, with those working moderate amounts of overtime smoking less than both those who worked low or high levels of overtime. Radi, Ostry and LaMontagne (2007) studied smoking status and intensity among a cross-sectional sample of 1101 Australians from the state of Victoria. They found that long working hours (50 or more per week) were associated with a higher propensity to smoke among men (but not greater smoking intensity).…”
Section: Introductionmentioning
confidence: 99%
“…For example, low decision latitude, low rewards relative to effort, and other psychosocial stressors at work have been associated with leisure time inactivity, obesity, and tobacco and alcohol consumption. [78][79][80][81][82][83][84][85][86][87][88][89][90] In turn, such combinations of risk factors may challenge health even further; examples are the interaction of cigarette smoking with physically heavy jobs on the risk of vertebral pathology, 91 and that of body mass index with physical workload on the risk of chronic shoulder disorders. 92 Thus, to be effective, WHP programs should address organizational conditions 93,94 involve employees in decisions about work processes, promote learning, reward appropriately, and attend to interpersonal relationships.…”
Section: -33mentioning
confidence: 99%